Ovoid foveal hyperreflective lesions as a sign of familial adenomatous polyposis: A case series and review - Serena Shah; Francisco Lopez-Font; Davina Malek; Jason Fan; Natasha Ferreira Santos da Cruz; Catherin Negron; Basil K. Williams, Jr.; Audina M. Berrocal (American Journal of Ophthalmology Case Reports)
Purpose: To report 2 cases of presumed retinal hamartoma (RH) in pediatric patients with genetically-confirmed familial adenomatous polyposis (FAP), both evaluated by optical coherence tomography (OCT) and one evaluated with optical coherence tomography angiography (OCTA). Observations: A six-year-old girl presented with occasional blurry vision in the left eye. OCT showed a foveal hyperreflective lesion with disruption of photoreceptors and retinal pigment epithelium (RPE). A nine-year-old female with a past medical history of FAP presented with progressively decreasing vision and floaters in the right eye for the past 6 months. OCT showed a well-demarcated hyperreflective ovoid lesion in the fovea. OCTA revealed no flow signal within the lesion, as well as a second smaller hyperreflective lesion temporal to the fovea. Both patients were diagnosed with presumed retinal hamartoma in the setting of FAP. Conclusions and Importance: Presumed RH can occur in genetically-confirmed, pediatric FAP. On OCTA imaging, these lesions show no intrinsic vascularity. Evaluation with OCT and knowledge of foveal changes in these patients can help identify underlying systemic disease.